Union Endorsements and the Voting Intentions of Union Members in Canada - Savage, Larry; Westlake, Daniel (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2025)
This article explores the impact of union endorsements on the voting intentions of union members in Canada. Through a survey of union members, the study reveals that while union endorsements generally do not significantly influence voting behaviour, satisfaction with one’s union enhances the likelihood of supporting union-endorsed candidates in federal, provincial, and local elections. This correlation underscores that having strongly supported unions in the workplace helps to build strong unions in the political arena with improved capacity to deliver union members’ votes. The findings also provide a basis for further research on the potential electoral significance of union endorsements.